Discussing the Cutting Method of Skew Bevel Bear based on the Tooth Surface Generating Line - Baichao Wang; Xianting Lu; Litong Zhang; Zhenquan Xu; Xue Zhang (Jixie chuandong)
The principle of tooth surface generating of skew bevel gear is analyzed about spherical involute， based on the theory that the line which in the plane that is tangent with the base cone of the skew bevel gear roll on the cone surface absolutely， a new milling method of gear surface is put forward. In this method， the alignment line obtained by the vertical intersection of the edge end circle and the base plane of the disk milling cutter is the tooth surface generation line， the relative motion between tool and workpiece is realized by using the relative motion relation generated by tooth surface. By analyzing the tooth surface generation motion， the machining motion process model of the tool and the workpiece is established. The tooth surface cutting is realized by the way of three-axis linkage of machine tool. The device for cutting test of skew bevel gear is designed and the correctness and feasibility of the method are verified by cutting test.